To the Rhythm of Silence: Music as a Producer of Psychological Processes - Monteiro Ribeiro, Ana Rita; Gonçalves, Carlos Manuel (Pensando Psicología, 2017)
Introduction: An extended theoretical review of various fields of knowledge made us conceive the possibility that music could be a privileged device in understanding the development of human psychological structures and a driving force for change. Purpose: This possibility led us to outline the following objective: To understand how music, as an art, may possess elements that enhance psychological and emotional development. Method: Thus, a study was designed based on a quantitative methodology, in order to evaluate the impact of musical training on three psychological processes: empathic processing, differentiation ability, and emotion regulation. Three instruments were administered to a sample of 237 subjects: The Interpersonal Reactivity Index, the Emotion Differentiation Repertoire and Ability Assessment Scale, and the Emotion Regulation Questionnaire. Results: While there were no significant differences between listeners and performers, the study allowed an in-depth understanding of how gender can determine empathic processing and the use of adaptive emotion regulation strategies; academic progression can influence the way of interpreting and acting on the environment. Conclusion: Commitment to music, no matter how, can be sufficient to promote certain psychological processes.